(untitled) (Bangladesh Journal of Plant Taxonomy, 2017)
The study focuses the plant diversity in different habitats, status and percentage distribution of plants in Sonadia Island, Moheshkhali, Coxs Bazar of Bangladesh. A total of 138 species belonging to 121 genera and 52 families were recorded and the species were categorised to tree (56 species), shrub (17), herb (48) and climber (17). Poaceae represents the largest family containing 8 species belonging to 8 genera. Homestead vegetation consists of 78% species followed by roadside (23%) and cultivated land (10%), mangroves (9%), sandy beaches (4%) and wetland (1%). The major traditional use categories were timber, food and fodder, fuel, medicine and fencing where maximum plant species (33% of recorded) were traditionally being used for food and fodder. Keywords: Plant Diversity; Ecologically Critical Area; Sonadia Island; Mangroves. Bangladesh J. Plant Taxon. 24(1): 107116, 2017 (June)